THE INFLUENCE OF FINANCIAL LITERACY ON INDIVIDUAL FINANCIAL MANAGEMENT PATTERNS - Sultan Albani Toha; Erlangga Mulya Lesmana; Daffa Tris Sriprasta; Wiranta (International Journal of Multidisciplinary Reseach, 2026)
Financial literacy has become an essential competency in modern society, particularly in an era characterized by rapid technological advancement and increasing access to financial services. Individuals are now exposed to various financial products such as digital banking, online investments, and instant credit facilities. While these developments provide convenience, they also require individuals to possess adequate financial knowledge and skills to manage their financial resources effectively. This study aims to analyze the influence of financial literacy on individual financial management behavior using a descriptive quantitative approach. The study utilizes secondary data derived from national surveys and relevant academic literature. The findings indicate that financial literacy plays a significant role in shaping financial behavior. Individuals with higher financial literacy tend to demonstrate better financial management practices, including budgeting, saving, and making informed financial decisions. Conversely, individuals with low financial literacy are more likely to engage in poor financial behaviors, such as excessive consumption, lack of financial planning, and inefficient use of financial services. The study concludes that improving financial literacy is crucial in enhancing financial well-being and promoting responsible financial behavior among individuals.